The intersection of autoimmunity and neurology: insights from a case of striatal lupus encephalitis - Soo, Tze Hui; Suppiah, Subapriya; Zamri, Muhammad Furhan (Springer Science and Business Media LLC, 2024)
Systemic lupus erythematosus (SLE) is a multifactorial autoimmune disorder predominantly affecting women, characterized by the production of autoantibodies against various nuclear antigens, leading to widespread immune dysregulation and multisystem involvement. Among its complex manifestations, neuropsychiatric systemic lupus erythematosus (NPSLE) represents a particularly challenging aspect of the disease due to its wide spectrum of neurological and psychiatric symptoms. This case report presents a rare instance of striatal lupus encephalitis, a severe subtype of NPSLE, in a 32-year-old woman, highlighting its distinct clinical and radiological features. The patient initially developed bilateral ocular occlusive vasculitis and later presented with acute right-sided hemiparesis and facial asymmetry. Magnetic resonance imaging (MRI) revealed bilateral symmetrical T2-weighted and fluid-attenuated inversion recovery (FLAIR) hyperintense signals in the basal ganglia, consistent with striatal lupus encephalitis. No white matter hyperintensity or vasculitis changes were seen. Cerebrospinal fluid analysis revealed markedly elevated protein levels, though no infectious organism was identified. The patient was treated with high-dose prednisolone, alongside empirical antibiotic and antiviral therapy to address potential meningoencephalitis. Remarkably, she made a full recovery from her stroke-like symptoms. Despite its rarity, the identification of striatal lupus encephalitis is critical due to the severe and potentially irreversible nature of the neurological damage. This case underscores the importance of a comprehensive diagnostic approach, integrating clinical, serological, and neuroimaging findings to differentiate striatal lupus encephalitis from other neuropsychiatric conditions associated with SLE. Its management typically involves aggressive immunosuppressive therapy, with intravenous methylprednisolone being the first-line treatment. The case also illustrates the potential for recovery with prompt and appropriate treatment, as evidenced by the complete resolution of neurological symptoms and MRI findings at follow-up.